Radiologic findings of primary pulmonary angiosarcoma: A case report. Issue 25 (June 2018) - Ma, Jianbing; Zhang, Weiqiang; Huang, Yijuan; Wang, Lizhang; Wang, Jia; Yuan, Linna; Zhang, Jingfeng
Abstract: Rationale: Primary pulmonary angiosarcoma is a rare disease. Here, we report the case of primary pulmonary angiosarcoma diagnosed computed tomographic pulmonary angiography (CTPA) and discuss its specific imaging characteristics. Patient concerns: A 46-year-old man was admitted for cough and shortness of breath. Thoracic CTPA images demonstrated a high-attenuation lesion surrounding by a halo sign in upper lobe of right lung, and the dilated vessel was also seen in lower lobe of right lung. The sign of "hillside sign" was observed on CTPA. Diagnoses: It was diagnosed with primary pulmonary angiosarcoma. Interventions: Right thoracotomy and right upper lobe lobectomy were performed. Outcomes: Five years later, the patient dead of complete occlusion of the pulmonary artery owing to tumor recurrence. Lessons: Although primary pulmonary angiosarcoma is a rare disease with atypical early clinical symptoms, and it is often misdiagnosed as pulmonary embolism and pulmonary infection. Therefore, it is important to recognize the CTPA imaging characteristics of primary pulmonary angiosarcoma and Surgical resection should be performed to prolong the patients' lifetime.